Margarine as a Value-Added Product from Fish Oil, A By-Product of Lemuru Fish Canneries - Wardhani, Citra Rachmania; Alamsjah, Mochammad Amin; Sulmartiwi, Laksmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Lemuru fish (Sardinella lemuru) is rich in omega-3 so it is widely used as raw material for fisheries production such as fish canning which produces by-products in the form of crude fish oil which needs to be purified by adding adsorbents so that it becomes pure fish oil. The adsorbent that can be used in the purification of fish oil is activated charcoal. Fish oil can be used as raw material for making added value products such as margarine. The aim of this study is to analyse the characteristics of margarine as a value-added product made from fish oil. Research shows that purification with activated charcoal produces fish oil with %FFA and PV that are in accordance with IFOS. Fish oil margarine in this study showed organoleptic value of colour 7.4 and aroma 7.07, emulsion stability 100%, %FFA content 0.28 Â± 0.08, PV 1.6 Â± 0.173, and higher 0.39% EPA and 2.58% DHA content compared to commercial margarine. In previous study showed margarin from sardine fish oil contains 19.5% EPA and 10.5% DHA which is also not found in commercial margarine from palm oil. The difference in EPA and DHA content between this study and previous study may be due to the fact that the fish oil in this study was obtained from by-products of canning processing with high temperatures which may cause a decrease in fatty acid levels due to protein denaturation.